Bio-pharmaceuticals : emerging proniosomes in drug delivery - Nanjwade, Basavraj K.; Singh, Jeet; Ahmad, Kausar; Manvi, F. V. (Nova Science Publishers, 2011)
Vesicular drug delivery system like liposomes and niosomes, sometimes drugs are not delivered in a desired manner because of aggregation, sedimentation, stability problems and tedious method of production. By using ‘Proniosomes’ as carrier for drug delivery these problems of drug delivery can be reduced because they are easy to prepare and having good physical and chemical stability. Proniosomes also have been shown wide applicability in pharmaceutical and medical field; they are promising carrier for systemic and controlled delivery of drugs. Entrapment in the lipidic or core material of the proniosome can help in the delivery of drugs with poor solubility, lower permeability and first pass effect. Proniosome are also useful for the delivery of hydrophobic and amphiphilic drugs. In the present review various methods used in proniosome preparation are discussed. A brief focus on characterization parameters, factors affecting preparation and applications are presented.